Hubungan Antara Persepsi dan Partisipasi Mahasiswa Dalam Perkuliahan Daring Selama Masa Pandemi Covid- 19 (Studi Kasus Pada Mahasiswa Prodi Akuntansi UNP Kediri - Mar’atus Solikah; Dian Kusumaningtyas (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2021)
Abstract In the midst of the Covid-19 pandemic, the education sector is a sector that must continue to operate, including at the university level. One of the efforts so that the learning process can still take place effectively is by means of online (online). In its implementation, there are still obstacles that are somewhat worrying both among students, lecturers and universities themselves, especially those related to student perspectives and participation. The purpose of this study was to analyze the relationship between student perceptions and participation in online lectures during the Covid-19 pandemic. This research is a case study using a questionnaire instrument given to students of the Accounting Study Program of UNP Kediri. The results of the analysis obtained that there is a relationship between the teaching and learning process and student participation which is 0.406 indicating a positive number, then for lecturer competence there is also a correlation between lecturer competence and student participation which is 0.623 indicating a positive number, and there is a correlation between infrastructure and student participation. of 0.453 indicates a positive number.